Decision Support for a Housing Mobility Program Using a Multiobjective Optimization Model - Johnson, Michael P.; Hurter, Arthur P. (Management Science, 2000)
As result of public housing reform and welfare reform, the operating environment of public housing authorities has changed significantly. Given these policy initiatives, housing mobility programs represent viable strategies for providing public housing residents with access to economically healthy, integrated neighborhoods. In this paper we present a decision support methodology to assist the design of housing mobility programs. This methodology incorporates economic models for estimating dollar-valued impacts associated with tenant relocation, and a multiobjective optimization model for generating alternative relocation schemes associated with various objective function weights. Using data for Lake County, Illinois and Chicago, we demonstrate that nondominated allocations represent significant trade-offs between dollar-valued and non-dollar-valued policy objectives; existing distributions of subsidized housing represent suboptimal solutions to the housing relocation problem; and increases in available rental housing can result in housing dispersion schemes that have positive net economic benefits relative to the status quo.